Review of Track Gauge for Trans-Sumatera Railway Revitalization and Development - Soemino Eko Saputro; Prasadja Ricardianto; Haniva Mulyani; Primadi Candra Susanto (Jurnal Penelitian Transportasi Darat, 2020)
The aim of this research is to comprehend in details how revitalization and development of railway infrastructure on the Trans-Sumatera line in Sumatera Island. The main problem in this research is that the use of railways in Sumatera Island is neither sustainable nor in all provinces. This research is both meta-analytical, by exploring the existing journals, and factual as a phenomenon in the utilization of spoor width that happens in the world today. It is completed by parameter or performance indicators as for benchmarking with other countries. From the result of this research, the data shows that almost 60 percent of existing railway tracks around the world have been installed with standard gauge of 1,435 mm and have been international standard. The benefit of this study is that the leaders or decision makers can take it into account to support the future transportation in Sumatera Island which must be oriented to bigger, faster, safer, cleaner, cheaper, affordable, and leisure. To keep exploiting the existing railway or track can be done by developing construction equipment of track gauge adjuster to change the wheel gauge from 1,435 mm to 1,067 mm. Subsequently re-gauging is done in stages, changing the track gauge from narrow gauge of 1,067 mm to standard gauge of 1,435 mm.